Influences of the number of non-consecutive joints on the dynamic mechanical properties and failure characteristics of a rock-like material. (April 2023) - Li, Xiaoshuai; Gao, Wenxue; Guo, Lianjun; Li, Zhuo; Zhang, Shenghui
Highlights: A series of physical model tests were carried out on the dynamic mechanical properties and failure characteristics of rock-like materials with different numbers of non-consecutive joints. The effects of the number of non-consecutive parallel joints on the shape of the stress–strain curve, dynamic peak strength, and energy dissipation characteristics of rock-like materials were systematically studied. The deterioration mechanism of pore structure under external loading and the influence of the number of joints on pore structure were quantitatively analyzed from the microscopic point of view. The cracking process of rock-like material specimens with different numbers of non-consecutive parallel joints was studied. Abstract: The dynamic mechanical properties and failure characteristics of jointed rocks are the focus of research in rock engineering. In this study, cement mortar specimens with 0–4 parallel non-consecutive joints were prepared. The split Hopkinson pressure bar (SHPB) was used for dynamic impact testing of prepared specimens. Nuclear magnetic resonance (NMR) was used to detect the pore structure deterioration of the specimens after impact. Finally, the failure characteristics of the specimens were studied by extracting the surface cracks of the specimens. The results show that the number of non-consecutive joints have a significant effect on the dynamic mechanical properties of cement mortar specimens. The increased number of joints will change the stress–strain curve from a single-peak shape to a multi-peak shape and enhance the ductility. The dynamic peak strengths and the proportion of dissipated energy of the specimens decrease with the increase of number of joints, but the magnitude of change decreases gradually. NMR analysis reveals the pore structure alterations of the specimens. After being impacted, the internal pores of the specimens increase significantly, especially the macro-pores and micro-pores. Some micro-pores become meso -pores and macro-pores, and some pores are connected. These changes of microscopic pore structure lead to macroscopic failure of specimens. A quantitative analysis of the porosity of the specimens shows that the rate of change in porosity is in direct proportion to the number of joints, which means that the greater the number of joints, the larger the damage degree of the specimens. The failure characteristics of the specimens indicate that tensile stress mainly dominates the fracture behavior of the specimens, while shear stress has limited damage to the specimens. After the tensile wing cracks start from both tips of the joint, they extend along the rock bridge to the adjacent joint or the end of the specimen. After the wing cracks coalesce, they form a rectangular failure zone. In addition, axial tensile cracks will start near the middle of the first joint and the middle of the last joint, extending to the top and bottom of the specimen, respectively. Slight shear cracks only develop at the joint ends.